Botanic Origin of Propolis Extract Powder Drives Contrasted Impact on Diabesity in High-Fat-Fed Mice - Nicolas Cardinault; Franck Tourniaire; Julien Astier; Charlene Couturier; Lauriane Bonnet; Eva Seipelt; Esma Karkeni; Claire Letullier; Naima Dlalah; Stephane Georgé; Lourdes Mounien; Jean-Francois Landrier (MDPI AG, 2021)
Propolis extracts are considered as nutraceutical products with potentialities towards obesity and comorbidities management. Nevertheless, propolis extracts composition is highly variable and depends on the botanic origin of plants used by the bees to produce propolis. This study aims to evaluate the differential effect of poplar propolis extract powder (PPEP), Baccharis propolis extract powder (BPEP), and/ or Dalbergia propolis extract powder (DPEP) on obesity and glucose homeostasis in high-fat-fed mice. PPEP supplementation reduced high-fat (HF)-mediated body weight gain, adiposity index, and improved glucose homeostasis in male C57Bl/6J mice that were submitted to a high-fat diet for 12 weeks, whereas BPEP, DPEP, or a mix of the three PEPs did not modify those parameters. Adipose tissue (AT) gene expression profiling highlighted an induction of mRNA related to lipid catabolism and an inhibition of mRNA coding for inflammatory markers. Several Nrf2 target genes, coding for antioxidant enzymes, were induced in AT under PPEP effect, but not by other PEP. Interestingly, representative PPEP polyphenols mediated the induction of Nrf2 target genes cell-autonomously in adipocytes, suggesting that this induction may be related to the specific polyphenol content of PPEP. Whereas PPEP supplementation has demonstrated a clear potential to blunt the onset of obesity and associated comorbidities, other PEPs (from Baccharis and Dalbergia) were inefficient to support their role in preventive nutrition.